Low-Cost Vehicle Security System Using Location Change and Vehicle Status Based on Internet of Things - Afandi, Mas Aly; Purnama, Sevia Indah; Wibisono, Gunawan (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
Motor vehicle theft is a crime that can potentially harm the owner of the vehicle. This crime should be anticipated, and a security system should be implemented to avoid vehicle theft. Research about vehicle security systems has run into an uptrend. Previous research has already developed security system devices for vehicles with many peripherals. This study aims to develop a new low-cost vehicle security device with location change calculation to cut unused peripherals. The proposed device has a logic checker, horn controller, and vehicle controller as security systems. According to the testing result, the device can detect the vehicle status from off to on while the security system is active. The device will turn on the horn and turn the vehicle off. This function always works at 100%. This device also detects theft according to the location change. This feature works at a 100% rate, with an average error reading location of 4,83m and an average error distance calculation of 0,91m. This distance is tolerable because the owner can still see the vehicle. This research result proves that the device can be used to secure the vehicle. This device's performance will increase if placed outside the building. The data was also successfully sent to the IoT platform without data loss or incomplete data. Compared with other research, the proposed device has fewer peripherals with the same or more security features.